Critical Thinking and Pedagogy in the Indian Education System: Highlighting Socio-cultural Dissent - Shams, Anam; Ahmad, Farhan; Khalid, Sadaf; Banu, Sameena (Journal of Education Culture and Society, 2025)
Thesis. The study foregrounds reaffirming the essential requirement that students acquire critical thinking skills in order to question the political action around them, comprehend its contradictions and complexities, identify the shortcomings of mainstream solutionism, and consider their roles within power structures and change initiatives. Concept. This present study challenges and offers a framework for a critical-creative pedagogy that creates such avenues for exploration both inside and outside of Indian higher education. The question of what kind of education is necessary to prepare students of all ages to take on global educational concerns is also raised by efforts made in the study. Results and conclusion. By fostering critical-creative pedagogies, Indian higher education can produce students who are not just knowledgeable but also active, engaged, and capable of effecting meaningful social change. Thus, education can transform individuals and society, offering hope and action amid uncertainty and complexity. However, considering how little state and education systems are doing to teach young minds the value of civic engagement and how to participate more actively in the Indian democracy, maybe this is not all that shocking. Originality. Such critical teaching, mainly when it is the only focus of classroom engagement, can cause students in some disciplines, like international relations and local-level public policy, to become disillusioned about the potential for their education to drive transformative change, a goal that initially inspired them to pursue university education.